Gambaran Ct Value pada Swab Pertama dan Swab Kedua Covid 19 pada Anak di Indramayu - Warih Kuncoro Mukti; Indriani Silvia; Donny Nauphar (Universitas Muhamadiyah Manado, 2026)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The first case was identified in Wuhan, China, in December 2019. The World Health Organization declared COVID-19 a Public Health Emergency of International Concern (PHEIC) on January 30, 2020, and a pandemic on March 11, 2020. This study aimed to determine the results of CT Value images on the first and second swab tests of children with COVID-19 in Indramayu. A descriptive design was used with total sampling, involving 54 respondents. Secondary data were analyzed using univariate analysis. On the first swab test, 27 children (50.0%) had a strong positive Ct Value, 26 children (48.1%) were positive, and 1 child (1.9%) had a weak positive Ct Value. On the second swab test, 23 children (71.9%) were positive, 6 children (18.8%) were strong positive, and 3 children (9.4%) were weak positive. All children tested positive on the first swab, while 32 (59.3%) remained positive and 22 (40.7%) became negative on the second swab. Most children showed decreased infection severity, although some remained positive.